Regulation of Cytochrome P450 enzyme activity and expression by Nitric Oxide in the context of inflammatory disease - Morgan, Edward T. (Drug Metab Rev, 2020)
Many hepatic cytochrome P450 enzymes and their associated drug metabolizing activities are down-regulated in disease states, and much of this has been associated with inflammatory cytokines and their signaling pathways. One such pathway is the induction of inducible nitric oxide synthase (NOS2) and generation of nitric oxide (NO) in many tissues and cells including the liver and hepatocytes. Experiments in the 1990s demonstrated that NO could bind to and inhibit P450 enzymes, and suggested that inhibition of NOS could attenuate, and NO generation could mimic, the down-regulation by inflammatory stimuli of not only P450 catalytic activities but also of mRNA expression and protein levels of certain P450 enzymes. This review will summarize and examine the evidence that NO functionally inhibits and down-regulates P450 enzymes in vivo and in vitro, with a particular focus on the mechanisms by which these effects are achieved.